Aerosol chemical composition and light scattering during a winter season in Beijing. (June 2015) - Tao, Jun; Zhang, Leiming; Gao, Jian; Wang, Han; Chai, Faihe; Wang, Shulan
Abstract: To evaluate PM2.5 contributions to light scattering under different air pollution levels, PM2.5 and its major chemical components, PM10, size-segregated water-soluble ions, and aerosol scattering coefficient (bsp ) under dry conditions were measured at an urban site in Beijing in January 2013 when heavy pollution events frequently occurred. Measurements were categorized into three pollution levels including heavy-polluted (Air Quality Index (AQI) ≥ 200), light-polluted (200 > AQI ≥ 100) and clean periods (AQI < 100). The average PM2.5 mass concentration was 248 μg m −3 during the heavy-polluted period, which was 2.4 and 5.6 times of those during the light-polluted (104 μg m −3 ) and clean (44 μg m −3 ) periods, respectively. The concentrations of SO4 2−, NO3 − and NH4 + increased much more than those of OC and EC during the heavy-polluted period compared with those during the light-polluted and clean periods. Good correlations between PM2.5 and bsp were found (R 2 > 0.95) during the different pollution levels. The mass scattering efficiency (MSE) of PM2.5 was 4.9 m 2 g −1 during the heavy-polluted period, which was higher than those during the light-polluted (4.3 m 2 g −1 ) and clean periods (3.6 m 2 g −1 ). To further evaluate the impact of individual chemical components of PM2.5 on light scattering, a multiple linear regression equation of measured bsp against the mass concentration of (NH4 )2 SO4, NH4 NO3, Organic Matter (OM), EC, Fine Soil (FS), Coarse Matter (CM) and Other chemical compounds were performed. (NH4 )2 SO4, NH4 NO3 and OM were the dominant species contributing to bsp under both dry and ambient conditions. OM contributed more to bsp than the sum of (NH4 )2 SO4 and NH4 NO3 did under the dry condition during all the pollution periods and this was also the case under the ambient condition during the light-polluted and clean periods. However, the total contributions of (NH4 )2 SO4 and NH4 NO3 to bsp under the ambient condition was 55%, much more than the 29% contribution from OM during the heavy-polluted period. High (NH4 )2 SO4 and NH4 NO3 concentrations and their hygroscopicity were the main reasons causing visibility degradation during the heavy-polluted period, and the effect can be enhanced under high RH conditions. Highlights: Aerosol chemical and optical properties were compared in different pollution levels. Contributions of dominant chemical components to light scattering were quantified. Causes of heavy pollution events and related visibility degradation were explored.